An analytical method for a pile-stabilised slope considering soil anisotropy. Issue 6 (11th December 2020) - Zhuang, Yan; Cui, Xiaoyan; Dai, Guoliang; Geng, Xueyu; Li, Shuai
Abstract : The use of stabilising piles is an effective method of reinforcing a slope against landslides. Soil arching between the piles promotes more load transfer into the piles, thus improving slope safety. However, few analytical solutions have been proposed for assessing the safety of an anisotropic slope with soil arching between stabilising piles, especially in most current design procedures. Based on BS 8006-1:2010, an analytical method was developed to evaluate the stability of a slope reinforced with stabilising piles, taking the anisotropy of soil strength and the horizontal soil-arching effect into account. A field case was used to assess the results of the proposed analytical method; differences of approximately 0·6–8·9% were found. To validate the proposed analytical method, a three-dimensional numerical simulation considering soil anisotropy was conducted; variation of the soil cohesion with depth and the direction of principal stress was introduced into the numerical analysis. The safety factors predicted by the numerical simulation agreed well with those derived by the proposed analytical method, with differences of 0·7–17%. The safety factor was found to decrease with increasing anisotropy coefficient and increase with higher effective cohesion and effective friction angle.